2011
DOI: 10.3111/13696998.2010.547967
|View full text |Cite
|
Sign up to set email alerts
|

Study of the incremental cost and clinical burden of hip fractures in postmenopausal women in the United Kingdom

Abstract: The results of this study indicate that the cost and clinical burden associated with hip fractures in postmenopausal women in the UK are considerable. The incremental cost is mostly related to the cost of hospitalization and treatment of the hip fracture. Key limitations were the inclusion of only those women with a recorded hospitalization, and that costs associated with rehabilitation services, social services, and long-term care were not recorded in this study, although these are important contributors to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…One in two women and one in five men aged fifty and over in the UK will suffer a fracture in their lifetime [1]. Osteoporotic fractures commonly occur at the hip, spine, and wrist and of these hip fractures have the highest short-term mortality, morbidity and associated socioeconomic impact [2][3][4]. Regular exercise is widely recommended as the most effective nonpharmacological method for improving and maintaining BMD [5] and can also reduce the risk of falling.…”
Section: Introductionmentioning
confidence: 99%
“…One in two women and one in five men aged fifty and over in the UK will suffer a fracture in their lifetime [1]. Osteoporotic fractures commonly occur at the hip, spine, and wrist and of these hip fractures have the highest short-term mortality, morbidity and associated socioeconomic impact [2][3][4]. Regular exercise is widely recommended as the most effective nonpharmacological method for improving and maintaining BMD [5] and can also reduce the risk of falling.…”
Section: Introductionmentioning
confidence: 99%
“…137,149 When the results of these previous studies were inflated to 2012-13 prices, we found considerable variability in the reported 1-year costs after hip fracture, with estimates between £6176 137 and £20,470. 137,149 However, these studies focused solely on women with hip fractures. Hence our study contributes significantly to the evidence base regarding hip fractures by identifying and following large populations of hip fracture patients in primary and hospital care up to 2 years before and after the index event.…”
mentioning
confidence: 98%
“…micro costing or valuing HRGs). These help to explain the significant variability in the reported costs; for example, the reported costs for acute inpatient admission with hip fracture varied from £4202 to £16,452 (2012-13 prices).Focusing on the four more recent studies, Gutiérrez et al 137 reported costs based on 2427 women aged > 50 years identified in a primary care research database. The time horizon of the analysis was 12 months post hip fracture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Health Improvement Network (THIN) database has been used to characterize the risk of fracture associated with several chronic conditions and drug exposures in adults and children (19)(20)(21)(22)(23)(24)(25)(26). The objectives of this large population-based study were to determine whether urolithiasis is associated with a higher risk of incident fracture and to delineate age and sex effects.…”
Section: Introductionmentioning
confidence: 99%